Homologs of the STYLISH gene family control nectary development in Aquilegia. Issue 2 (26th August 2018) - Min, Ya; Bunn, J. Imani; Kramer, Elena M.
Summary: Floral nectaries are an interesting example of a convergent trait in flowering plants, and are associated with the diversification of numerous angiosperm lineages, including the adaptive radiation of the New World Aquilegia species. However, we know very little as to what genes contribute to nectary development and evolution, particularly in noncore eudicot taxa. We analyzed expression patterns and used RNAi‐based methods to investigate the functions of homologs from the STYLISH ( STY ) family in nectar spur development in Aquilegia coerulea . We found that AqSTY1 exhibits concentrated expression in the presumptive nectary of the growing spur tip, and triple gene silencing of the three STY ‐like genes revealed that they function in style and nectary development. Strong expression of STY homologs was also detected in the nectary‐bearing petals of Delphinium and Epimedium . Our results suggest that the novel recruitment of STY homologs to control nectary development is likely to have occurred before the diversification of the Ranunculaceae and Berberidaceae. To date, the STY homologs of the Ranunculales are the only alternative loci for the control of nectary development in flowering plants, providing a critical data point in understanding the evolutionary origin and developmental basis of nectaries. Abstract : See also the Commentary on this article by Moyroud, 221 : 614–617 .